Erythrocyte adenylate kinase deficiency: characterization of recombinant mutant forms and relationship with nonspherocytic hemolytic anemia. - Abrusci, P; Chiarelli, L; Galizzi, A; Fermo, E; Bianchi, P; Zanella, A; Valentini, G (2007)
OBJECTIVE: Red cell adenylate kinase (AK) deficiency is a rare hereditary erythroenzymopathy associated with moderate to severe nonspherocytic hemolytic anemia and, in some cases, with mental retardation and psychomotor impairment. To date, diagnosis of AK deficiency depends upon demonstration of low enzyme activity in red blood cells and detection of mutations in AK1 gene. To investigate the molecular bases of the AK deficiency, we characterized five variants of AK1 isoenzyme-bearing mutations (118G>A, 190G>A, 382C>T, 418-420del, and 491A>G) found in AK-deficient patients with chronic hemolytic anemia. MATERIALS AND METHODS: The complete AK1 cDNA was obtained by standard procedures and using as template the reticulocyte RNA. The cDNA was cloned in a plasmid vector and the enzyme was expressed in Escherichia coli BL21(DE3)pLysS, and purified by standard protocols to homogeneity. DNA mutants bearing point mutations were obtained from the cloned wild-type cDNA using standard methods of site-directed mutagenesis, whereas the DNA mutant with deletion of codon 140 was obtained by a two-step method. RESULTS: Four mutant enzymes (Gly40Arg, Gly64Arg, Arg128Trp, Asp140del) were severely affected in activity, displaying a catalytic efficiency of four orders of magnitude lower than the wild-type; one (Tyr164Cys) was grossly perturbed in protein stability. CONCLUSIONS: The altered properties displayed by the mutant enzymes support the cause-effect relationship between AK1 mutations and hemolytic anemia.